Talent Identification of Future Sportsmen Using Sport Search Application - Utamayasa, I Gede Dharma (Budapest International Research and Critics University, 2021)
Sports coaching is a very important factor for advancing the world of sports. Without properly systemized scouting, the achievement stage will not be maximally achieved. This research aims to identify the sports talents of students at Wonorejo I/312 Primary School Surabaya and the dominant sports among the students. This quantitative research employed exploratory descriptive method. The research population included ten 6th grade students. Data obtained using 10 test types from Sport Search Aussie Sport Australia were identified and analysed. Based on the ranks, the results revealed the following sports talents: Diving, Gymnastics, Weightlifting, Indoor Cricket, and Powerlifting, which can potentially be developed.Â